Methionine deficiency promoted mitophagy via lncRNA PVT1-mediated promoter demethylation of BNIP3 in gastric cancer. (December 2021) - Xin, Lin; Lu, Hao; Liu, Chuan; Zeng, Fei; Yuan, Yi-Wu; Wu, You; Wang, Jin-Liang; Wu, Deng-Zhong; Zhou, Li-Qiang
Abstract: Background: The occurrence of recurrence and metastasis after treatment is a major challenge in the treatment of gastric cancer. This study was based on the methionine (Met)-dependent characteristics of gastric cancer cells to explore the effect of Met deficiency on the occurrence and development of gastric cancer. Methods: Human gastric cancer cell lines MKN45 and AGS and nude mice model were used to explore how Met affects gastric cancer by regulating lncRNA PVT1. Results: The levels of lncRNA PVT1 in gastric cancer cells and human gastric cancer xenografts of nude mice were down-regulated under the condition of Met deficiency. The cell viability and cell proliferation were declined after MKN45 and SGC-790 cells were cultured in Met-deficient medium. LncRNA PVT1 could affect BNIP3 promoter DNA methylation level through its interaction with DNMT1. Moreover, the silence of lncRNA PVT1 and the up-regulation of BNIP3 level inhibited the gastric cancer cell proliferation. Met deficiency could up-regulate BNIP3 expression by inhibiting the binding of lncRNA PVT1 to DNMT1, and activate mitophagy, thus inhibiting gastric cancer cell proliferation. Conclusion: Our study suggested that Met deficiency could down-regulate the expression of lncRNA PVT1, further demethylated the promoter of BNIP3, thus inhibiting the proliferation of gastric cancer cells by activating mitophagy. Graphical Abstract: ga1